2012
DOI: 10.1371/journal.pone.0030690
|View full text |Cite
|
Sign up to set email alerts
|

Optical Imaging of Disseminated Leukemia Models in Mice with Near-Infrared Probe Conjugated to a Monoclonal Antibody

Abstract: BackgroundThe assessment of anticancer agents to treat leukemia needs to have animal models closer to the human pathology such as implantation in immunodeficient mice of leukemic cells from patient samples. A sensitive and early detection of tumor cells in these orthotopic models is a prerequisite for monitoring engraftment of leukemic cells and their dissemination in mice. Therefore, we developed a fluorescent antibody based strategy to detect leukemic foci in mice bearing patient-derived leukemic cells using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Similar observations have been reported by other groups examining different models of solid tumors and leukemia [21]. That a convenient, reliable and sensitive tracking of myeloma cells is indeed valuable with whole body imaging techniques in living animals has been demonstrated by various groups [22,23].…”
Section: Discussionsupporting
confidence: 82%
“…Similar observations have been reported by other groups examining different models of solid tumors and leukemia [21]. That a convenient, reliable and sensitive tracking of myeloma cells is indeed valuable with whole body imaging techniques in living animals has been demonstrated by various groups [22,23].…”
Section: Discussionsupporting
confidence: 82%
“…However, the use of PET scanners in biosafety level 3 animal facilities is limited and we wanted to prove this approach was successful using fluorescent imaging and a well-established anatomical site of infection before embarking on these resource intensive experiments. Previous work in mice has shown that signal from fluorescently labeled probes correlates well to signal from identical probes imaged using bioluminescence imaging (BLI) or PET (31,34). The promising results reported here have given confidence in adopting this antibody-based fluorescent probe system to PET imaging.…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, we hypothesize that the probe was interfering with the establishment and spread of infection in those macaques given probe 1-or 2-days p.i. Similar interference with the biological process under study has been seen with other antibody probes (34). This underscores the need to carefully choose antibodies to be developed as probes, as those that interfere with the natural progression of infections will be less useful in studying pathogenesis.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…35 At no point in the present study did we experience any cellular deviations or changes in model pathogenesis in response to the pool of mAbs used. It was particularly encouraging that this imaging strategy gave better contrast than reporter gene imaging with GFP or bioluminescence in the time-domain configuration and could be used in multiple models of AML and in therapeutic settings.…”
Section: Discussionmentioning
confidence: 70%